Perbedaan Pemahaman Moral Antara Siswa Yang Mengikuti Ekskul Rohis dan Yang Tidak Mengikuti Ekskul Rohis - Fajriah, Redyna Fauziatul; , Dr. Wiwien Dinar Pratisti, M. Si, Psi (2017)
The purpose of this research was to determine the difference between the moral understanding of students who followed Rohis extracurricular and students who did not. The hypothesis of this study was "There is a difference between the moral understanding of students who followed Rohis extracurricular and who did not". Subjects in this study 80 were students of SMA Negeri 4 Surakarta, which consisted of the students who were from Rohis extracurricular and students who were not. The sampling methods was purposive random sampling study which was determined based on the characteristics of sample types. Measuring tool chwasusedin this study to reveal the research variables was the scale of moral understanding. Independent Sample t-Test or t test was used in this study as a data analysis methods. Based on the analysis results,thet value was 1.735 with a sign. 0.087 with 2 tailed. The significance was divided by 2 as the hypothesis was directional, therefore the obtained t value was 0.0435 (p <0.05). Thus it can be stated that there is a significant difference of moral understanding between students who followed Rohis extracurricular with students who did not. Students who followed Rohis extracurricular had an average value of empirical (RE) of 81.08. The condition was supported by the frequency that most of the subjects had high moral understanding. Conversely, students who did not Rohis extracurricular had an average value of empirical (RE) 78.43. This condition was also supported by the frequency that most of the subjects had high moralunderstanding. Therefore, students who followed Rohis extracurricular was different with students who did not follow as they had higher moral understanding.